A qualitative study on perception, attitude and apathy towards non-pharmaceutical precautionary measures against covid-19 among residents of Ibadan, Nigeria (2020)
COVID-19 emerged in Wuhan, China in December 2019 and within a short period of time it had become a pandemic that will go down in history as a one, perhaps non-intentional, biological warfare against humanity. It not only caused a global health crises but also a crisis in the political, economic, educational, entertainment (including sports, recreation, tourism) and other facets of human endeavours. COVID-19 has challenged the wittiness of biological, basic and applied scientists, educational, communication and other social scientists to bring their expertise on board to curtail its spread. It has also altered day to day national, international governance structures with serious global diplomatic and economic challenges and shrinks the gap between the rich, not so rich and poor nations as it exposes the vulnerabilities of all in response to its threats to lives and livelihoods. Serious efforts are going on to develop pharmaceutical interventions, nevertheless the most cost effective way out is non-pharmaceutical interventions of physical/social distancing, regular washing of hands, use of alcohol based hand sanitizers, consistent and proper use of face masks to halt or limit the spread of the virus. The researchers’ main objective was to unravel the perception, attitude and apathy of residents of Ibadan, Nigeria towards non-pharmaceutical precautionary measures against the spread of COVID-19. MATERIALS AND METHODS This was a qualitative study. It involved residents of Ibadan living around or in contact with the researchers, having been found by the researchers not to be observing non-pharmaceutical precautionary measures against COVID-19. Thematic analysis was done through identification, coding and categorizing patterns or themes in the data collected. RESULTS The study focused on perception, attitude and apathy towards precautionary measures among residents of Ibadan. Thirty people were interviewed, including 8 (26.6%) aged 20-30 years, 10 (30.3%) 31-40, 4(13.3%) 41-50 and 8 (26.7%) aged 51 years above. 19 (63.3%) were Christians while 11 (36.7%) were Muslims. On educational status, 6 (20.0%) had no formal education, 11 (36.7%) had secondary education while 13(43.3) had tertiary education .Most of the respondents, except a few, believed that COVID-19 was not real claiming to have only seen those that had been infected by the virus in the country on different media platforms such as on television and social media platforms. Many of the respondents had a positive attitude while some were indifferent claiming that they could never be infected no matter how they lived their lives. Majority claimed that it was almost impossible to maintain social distance as they had to go out in public cars, visit markets and also visit relatives who would not understand them if they decided to keep social distance. CONCLUSION The study revealed good perception of the disease, poor attitude and apathy towards many aspects of the use of non-pharmaceutical precautionary measures